Improving cognitive impairment among dementia users using mobile application: An initial study - Hassan, N.A.M.; Aslina Baharum; Ismail, R.; Zain, N.H.M.; Daruis, D (2020)
Computers such as mobile applications could play an important part in improving the quality of life for people with dementia: for information seeking, communication and leisure. Computers and the Internet offer special tools that could help people to maintain and learn new skills, develop hobbies and communicate with others in new ways. However, the design of interfaces often acts as a barrier to people with cognitive difficulties. Besides, mobile applications have been developed as tools in the diagnosis of dementia and the potential for using computers for activities in care settings is being recognized. However, very little research has been done into what people with dementia themselves need from computer interface design. Cognitive impairment includes the lacking ability to remember things, disorientation in remembering the current location and the struggle to find the correct word. People with dementia are often involved in this impairment. With that being said, this project proposes the use of a mobile application to help in improving their cognitive issues. Thus, this paper presents an initial study to tackle this problem, features and functionality of a mobile application specifically for dementia users are identified which contributes to the development of a diary application. Identifying and gathering features from previous studies is the initial method by hopes that may improve the dementia application for future development. © 2020, World Academy of Research in Science and Engineering. All rights reserved.